Karakteristik Organoleptik Pada Sirup Jeruk Gerga (Citrus nobilis SP.) dengan Variasi Konsentrasi Sari Buah dan Kadar Gula - Inka Rizki Padya; Desy Rahmayati (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this study was to determine the effect of the concentration of gerga orange juice and the percentage of fructose sugar on the organoleptic value of gerga orange syrup. The design used was a completely randomized factorial design (RALF) with two treatments, namely the amount of gerga orange juice (A) and the weight of sugar (B) with 3 replications. The organoleptic test that was carried out was the hedonic test which included preference scores on aroma, color, texture, and taste. The results of the research on organoleptic analysis showed that the preference scores for color, texture and taste had a significant effect but did not have a significant effect on aroma. The results on the average organoleptic analysis of the panelists showed a preference value ranging from 3-4 (ordinary to like). These results indicate that the gerga orange syrup in this study is still acceptable to consumers.